A flanêrie noturna: de Baudelaire e Rimbaud a Roberto Piva - Andrade, Rangel Gomes de (2021)
In Paranoia, by Roberto Piva, it is presented to the reader the nocturnal city of São Paulo, observed through the eyes of a lyrical self in a delusional state. The poet offers an oniric itinerary through the capital, in which the morbid ambientation transfigures the inhabitants of the nightlife in images which transite between sacred and profane figurations. The mystic-erotic ecstasy follows the flânerie of the poetical self through the urban space deformed by the night. Departing from the notions of “night texts'' defined by Américo (2017), the Benjaminian concept of “profane illumination” (1994), and a brief prelude about the urban and nocturnal theme development in Charles Baudelaire and Arthur Rimbaud’s poetry, we intend to analyze two of the poems in Paranoia’s volume, entitled “Praça da República dos meus Sonhos” e “Visão de São Paulo à noite (Poema Antropófago sob Narcótico)”, through the optics of the night and the dream, in order to verify how those element enter the urban ambientation and what are the images produced by the lyrical self through the mentioned nocturnal vision of São Paulo.